Piano keyboard tutor - Choo, Angie (2016)
The purpose of this report is to research and develop a piano keyboard tutor system. The main objective of this project is to create a system that will bring convenience to people who are interested to learn a musical instrument but does not wish to spend excessive money on piano school or tutors. Therefore, this report provides literature reviews that describe various existing piano tutoring system based on research papers and systems in the market. After reading and understanding the related literature reviews, this project aims to create and generate ideas for the piano keyboard tutor system.